Broadsheets Single-sheet Publishing in the First Age of Print - Pettegree, Andrew (Library of the Written Word, 2017)
A landmark study of single-sheet publishing during the first two centuries after the invention of printing. Long disregarded as ephemera or cheap print, broadsheets emerge as both a crucial communication medium and an essential underpinning of the economics of the publishing industry.; Readership: Historians of the book, media history and news, bibliographers and librarians, and those interested in the politics, government, religion and literature of the early modern period.